The Effect of Scrapbook Media with a Deep Learning Approach on Historical Thinking Skills and History Learning Outcomes of Students at SMAN 14 Gowa - Abdul Naim; Patahuddin Patahuddin; Ahmadin Ahmadin; Bakhtiar Bakhtiar (MASI Mandiri Edukasi, 2026)
History learning in high schools, including at SMAN 14 Gowa, often emphasizes rote memorization of facts, leading to low historical thinking skills among students. This quasi-experimental pretest-posttest control group study tests the effect of Scrapbook media integrated with a Deep Learning approach on 11th-grade students' historical thinking skills and history learning outcomes, using a sample of 36 students (18 per experimental and control group) selected via purposive sampling from a population of 36. Instruments included essay tests for historical thinking, objective tests for learning outcomes, observation, and documentation, with data analyzed via the Shapiro-Wilk normality test, Levene's homogeneity test, and the independent t-test. Results revealed significant gains in the experimental group (historical thinking: mean pretest 55.67 to posttest 83.22; learning outcomes: 58.11 to 86.89) compared to the control group using infographics (historical thinking: 56.72 to 72.28; learning outcomes: 58.50 to 74.33), with mean differences of 10.94 (t=5.55, p=0.000) for historical thinking and 12.55 (t=7.69, p=0.000) for learning outcomes. Scrapbook media with Deep Learning proved more effective for student-centered history education.